PWE-051 Biological therapy for the treatment of pre-pouch ileitis: a retrospective experience from three centres. (8th June 2018) - Segal, Jonathan; Rottoli, Matteo; Felwick, Richard; McLaughlin, Simon; Vallicelli, Carlo; Bassett, Paul; Faiz, Omar; Hart, Ailsa; Clark, Susan
Abstract : Introduction: Pre-pouch ileitis (PPI) is inflammation of the ileum proximal to an ileoanal pouch, usually associated with pouchitis. This pattern of inflammation can extend for a significant distance proximally. The estimated frequency of PPI is 6%. Symptoms are non-specific but can include increased frequency, obstructive symptoms and bleeding. The treatment of pre-pouch ileitis as a specific entity has been poorly studied, but it is generally treated concurrently with pouchitis. This to our knowledge is the largest study to explore the effectiveness of biologics for the specific treatment of PPI. Methods: This was a retrospective observational study across three centres. Data were collected between January 2008 and February 2018 from two centres in the United Kingdom and one centre in Italy. Patients were censored at the last clinical encounter following their most recent biologic therapy or until they had pouch failure defined by the need for an ileostomy to relieve pouch related symptoms. Patients with PPI treated with a biologic were followed up until last clinical encounter. Outcomes included the presence of PPI following biologic therapy, pouch failure defined by the need for an ileostomy, and remission of PPI defined by the absence of any PPI on endoscopic and histological assessment within a year of biologic therapy. Result: There were 30 patients in our cohort. The median age at diagnosis of IBD was 27 years old (range 6–48). The median time from pouch formation to diagnosis of pre-pouch ileitis was 81.5 months (range 1–147). The median length of time a patient was on biologics at the censorship of the study was 12 months (range 2–62). On last endoscopic follow-up, 21/30 (70%) still had endoscopic and histological evidence of PPI, seven had achieved remission and two had no endoscopic follow-up. In our cohort 11 patients had an ileostomy after a median time from starting a biologic of 25 months (range 14–91). Of those who had their UC reclassified to CD, 3/10 (30%) had pouch failure compared with 8/19 (42%) who had UC (p=0.72). Conclusion: Biologics fail to achieve endoscopic and histological remission of PPI in the majority of patients. In a small proportion of patients, they may help to prevent deterioration in symptoms. In a large proportion of patients with pre-pouch ileitis, surgery may be required despite biologic use.